MENINGKATKAN KETERAMPILAN KERJA SAMA, BERPIKIR KRITIS, DAN MEMECAHKAN MASALAH MENGGUNAKAN MODEL PEDULI PADA MURID KELAS V SDN PANGERAN 1 BANJARMASIN - Azizah, Noor; Dwitalia Sari, Dessy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted based on the problem of poor student activity, cooperation abilities, critical thinking skills, problem-solving skills, and learning outcomes in Indonesian language acquisition. These conditions were produced by inadequate student participation in the learning process, poor adoption of novel learning models, and the suboptimal use of interactive learning resources. The study used the PEDULI learning approach, which is backed by Quizizz media, to solve these issues. 26 fifth-grade students from SDN Pangeran 1 Banjarmasin participated in three sessions of Classroom Action Research (CAR) during the second semester of the 2025–2026 school year. Observations of student and teacher activities, teamwork, critical thinking, problem-solving, and learning outcomes were used to gather data. The results demonstrated a gradual improvement in all observed aspects at each meeting. Teacher activities rose from 46% to 96%, student activities from 46% to 92%, cooperation skills from 42% to 88%, critical thinking skills from 38% to 88%, problem-solving abilities from 42% to 92%, and learning outcomes from 46% to 92%. These findings indicate that the PEDULI learning model supplemented by Quizizz media effectively increased the quality of the learning process and students’ learning outcomes in Indonesian language acquisition.